2015
DOI: 10.1016/j.marpolbul.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

A framework for the resilience of seagrass ecosystems

Abstract: Seagrass ecosystems represent a global marine resource that is declining across its range. To halt degradation and promote recovery over large scales, management requires a radical change in emphasis and application that seeks to enhance seagrass ecosystem resilience. In this review we examine how the resilience of seagrass ecosystems is becoming compromised by a range of local to global stressors, resulting in ecological regime shifts that undermine the long-term viability of these productive ecosystems. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
191
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(193 citation statements)
references
References 164 publications
(193 reference statements)
0
191
0
2
Order By: Relevance
“…The present study found strong correlative evidence that increasing presence of herbivory is associated with reduced epicover suggesting increased leaf turnover and higher resultant levels of resistance to potential impacts (e.g., poor water quality) (Unsworth et al, 2015). Attached flora or fauna on seagrass leaves has the potential to reduce photosynthetic rate due to shading (Oh et al, 2009).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The present study found strong correlative evidence that increasing presence of herbivory is associated with reduced epicover suggesting increased leaf turnover and higher resultant levels of resistance to potential impacts (e.g., poor water quality) (Unsworth et al, 2015). Attached flora or fauna on seagrass leaves has the potential to reduce photosynthetic rate due to shading (Oh et al, 2009).…”
Section: Discussionmentioning
confidence: 55%
“…The present study recorded that such attached material can cover over 60% of the leaf area. This shading reduces the capacity of the plant to resist the effect of any further shading from problems, such as periods of poor water quality (Unsworth et al, 2015). We recorded a significant negative correlation between the percentage of leaves bitten and total epiphyte and epibiont coverage.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These migrations are driven by biological (e.g., the need to mate) or ecological (e.g., low resources or optimal/suboptimal climate) factors (Gilmore et al, 2007;Robinson et al, 2009;Lascelles et al, 2014) and have important roles in habitat connectivity (Unsworth et al, 2015;Tol et al, 2017). For example, in the Coral Sea, off the northeast coast of Australia, nesting green sea turtles (Chelonia mydas) tagged in Australia migrate to international feeding grounds in New Caledonia and back to their nesting grounds in Australia, crossing state, national, and international boundaries as they migrate (Read et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While monocultures or low-diversity systems may expand most rapidly following a stress-induced population collapse, diverse systems are more resilient (Stachowicz et al 2013;Gustafsson, Boström, and Unsworth 2013). Resilient seagrass communities are, in turn, easier to protect, manage, and restore (Unsworth et al 2015). This highlights the importance of understanding SAV diversity, both natural and restored as transplants or through seeding.…”
Section: Outlook For the Twenty-first Centurymentioning
confidence: 99%